Customer Guilt and its Relation to Purchase Intention of Green Products: A Study to University ‘Green’ Activist Students - Septin Puji Astuti; Yasaroh Dyah Rakhmawati; Zulfanita Dien Rizqiana; Rizki Kusumawardhani (Jurnal Organisasi dan Manajemen, 2022)
Purpose – This paper aims to investigate the structural model of customer guilt, perceived customer effectiveness, self-monitoring, and green purchase intention. Methodology – The present study is a survey of university students in four universities in Greater Surakarta. These students are involved in student organisations such as scout and university student hiking club. PLS-SEM is implemented in this study to compute structural relationships among variables. Findings – The result shows that customer guilt and self-monitoring affect green purchase intention. However, this study cannot prove that perceived consumer effectiveness is the mediator of  customer guilt and self monitoring to green purchase intention. Originality – This study proposes a model for green purchase intention of specific groups of young people who are more aware of environmental issues.